1999
DOI: 10.1021/jf981065c
|View full text |Cite
|
Sign up to set email alerts
|

Dried Green and Purple Lavers (Nori) Contain Substantial Amounts of Biologically Active Vitamin B12 but Less of Dietary Iodine Relative to Other Edible Seaweeds

Abstract: Vitamin B(12) concentrations of dried green (Enteromorpha sp.) and purple (Porphyra sp.) lavers (nori) were determined by both Lactobacillus leichmannii ATCC 7830 microbiological and intrinsic factor chemiluminescence methods. The values determined by using the microbiological method (63.58 +/- 2.90 and 32.26 +/- 1.61 microg/100 g of dry weight) were identical to those found by using the chemiluminescence method (69.20 +/- 2.21 and 25.07 +/- 0.54 microg/100 g of dry weight) in both dried green and purple laver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 13 publications
1
33
1
2
Order By: Relevance
“…These results are similar to those obtained by MacArtain et al 17 Ulva was also found to be a good source of B vitamins, richer than Wakame or Kombu in vitamin B 1 and B 2 . 22 It may also be an essential source of vitamin B 12 , especially for strict vegetarians, 23 who are commonly deficient in this vitamin, although the bioavailability of this vitamin is questionable for some investigators 24 but not for others. 25 However, B 6 and B 3 contents were very low.…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to those obtained by MacArtain et al 17 Ulva was also found to be a good source of B vitamins, richer than Wakame or Kombu in vitamin B 1 and B 2 . 22 It may also be an essential source of vitamin B 12 , especially for strict vegetarians, 23 who are commonly deficient in this vitamin, although the bioavailability of this vitamin is questionable for some investigators 24 but not for others. 25 However, B 6 and B 3 contents were very low.…”
Section: Resultsmentioning
confidence: 99%
“…Edible algae are known to be rich in vitamins, minerals and dietary fiber (14). The B12 in various edi ble algae was assayed by IF-based competitive inhibition methods and/or the microbiological method using L. delbrueckii ATCC7830 (14)(15)(16) (Table 1). Although dried green (Enteromorpha sp.)…”
Section: B12 Content In Edible Algaementioning
confidence: 99%
“…Dried green and purple laver have been the most popular selections of edible seaweed and also contain high amounts of vitamin B 12 . [33,34] Vitamin B 12 is most commonly found in animal sources and therefore are more difficult to obtain with lower meat consumption. [33] Surveys conducted by NHANES indicated a peak in meat consumption from ages 20-49 and a decrease in meat consumption in older age.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%